2022
DOI: 10.3390/cells11030443
|View full text |Cite
|
Sign up to set email alerts
|

Static Magnetic Fields Reduce Oxidative Stress to Improve Wound Healing and Alleviate Diabetic Complications

Abstract: Although some studies have shown that some static magnetic fields (SMFs) can promote wound healing in diabetic mice, it is not clear whether the other diabetes complications, such as liver disease and diabetic nephropathy, can also be alleviated. Here, we constructed two simple magnetic plates using neodymium permanent magnets to examine the comprehensive effects of moderate SMFs on genetically obese leptin receptor-deficient db/db diabetic mice. We found that although the blood glucose was not obviously reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 55 publications
(68 reference statements)
0
12
0
1
Order By: Relevance
“…For example, the diabetic chronic wounds are caused by the excessive ROS accumulation resulted from high levels of advanced glycation in the blood under persistent hyperglycinemia [ 29 ]. The excessive ROS accumulation in the wound can inhibit the function of macrophages and angiogenesis, thus hindering wound tissue regeneration and blood vessel reconstruction [ 30 ]. Moreover, the excessive ROS and RNS can directly or indirectly modify and degrade ECM proteins, leading to the impaired fibroblast and keratinocyte functions.…”
Section: Ros Generation and Its Pathogenic Roles In Oxidative Stress-...mentioning
confidence: 99%
“…For example, the diabetic chronic wounds are caused by the excessive ROS accumulation resulted from high levels of advanced glycation in the blood under persistent hyperglycinemia [ 29 ]. The excessive ROS accumulation in the wound can inhibit the function of macrophages and angiogenesis, thus hindering wound tissue regeneration and blood vessel reconstruction [ 30 ]. Moreover, the excessive ROS and RNS can directly or indirectly modify and degrade ECM proteins, leading to the impaired fibroblast and keratinocyte functions.…”
Section: Ros Generation and Its Pathogenic Roles In Oxidative Stress-...mentioning
confidence: 99%
“…A precise homeostatic control of oxidative state is essential for normal tissue repair while extreme (low or high) levels of ROS can impair wound healing [ 36 , 37 , 38 , 39 ]. Indeed, several studies indicated that reduced ROS level, by magnetic field or pro-oxidant enzyme deficiency, improved wound healing in a model of diabetic mice [ 34 , 40 ]. Furthermore, it has been well documented that non-healing wounds, due to diabetes, or chronic wounds characteristic of pathologies such as inflammatory bowel diseases, are associated with a higher ROS level [ 32 , 41 , 42 , 43 ].…”
Section: Good and Bad Wound Healing: Acute Versus Chronic And Chronol...mentioning
confidence: 99%
“…There were also no significant between-group differences for collagen fibril alignment and collagen fiber orientation. A recent study provided strong evidence supporting the role of SMF as a modality that accelerates wound healing in a diabetic mouse model that had experimentally induced 5 mm punch biopsy back wounds [ 20 ]. They pre-treated genetically obese leptin receptor-deficient db/db diabetic mice with seven weeks of continuous SMF exposure of about 15 mT at the wound site and continued treatment for three weeks post-wounding.…”
Section: Reviewmentioning
confidence: 99%